Status of Consumer Education and Financial Education in Canada (2016) - McGregor, Sue L. T. (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
This article reports on the status of consumer education in Canada in 2016 (junior and senior high), relative to the 2015-initiated federal national financial education/literacy strategy. Questions addressed: (1) Is it necessary to have separate financial education curricula when consumer education is available? and (2) Are the existing consumer education curricula adequate? After conceptualizing consumer education and literacy relative to financial education and literacy, a content analysis of provincial and territorial education documents identified 64 courses containing consumer-related content in seven subject areas. The majority (73%) of the 216 instances of consumer-related content—mostly (68%) found in home economics/family studies, social studies, mathematics, and business—pertained to resource management, with equal coverage for each of citizen participation (14%) and decision making (13%). Most (73%) of the courses were not offered until senior high. Results confirmed a fragmented and inconsistent approach to consumer education across subject areas, grade levels, provinces/territories, and regions. To stimulate dialogue, the national financial education strategy is framed as a stop-gap measure until there is political will for a pan-Canadian consumer education curriculum, predicated on the assumption that consumer education (not financial education) better prepares citizens for any future global depression. Appendix: McGregor Appendix